Mitigating transmit B1 inhomogeneity in the liver at 7T using multispoke parallel transmit RF pulse design - Wu, Xiaoping; Schmitter, Sebastian; Auerbach, Edward J.; Uğurbil, Kâmil; Van de Moortele, Pierre-François (Quantitative Imaging in Medicine and Surgery, 2014)
In this work, the use of multi-spoke slice-selective parallel transmit (pTX) RF pulse was explored to address B1+ inhomogeneity in the largest transverse section of the liver at 7T. The impact of the number of spokes was specifically investigated, considering RF pulses consisting of 2, 3 and 4 spokes, as well as singlespoke RF pulses corresponding to static B1 shimming. Healthy volunteers were imaged on a whole body MR scanner equipped with an eight-channel transmit system. A robust and fast transmit B1 (B1+) estimation method was employed to obtain the eight-channel B1+ maps within a single breath hold. Gradient echo (GRE) images of the liver were acquired using the four different RF pulses and the results were compared. The use of static B1 shimming (i.e., 1-spoke RF pulse) resulted in partial improvement but significant signal dropouts were still observed in the target region. By comparison, the use of multi-spoke pTX RF pulse design gave rise to much improved excitation homogeneity without signal dropouts. These results demonstrate the effectiveness of multi-spoke pTX RF pulse design in B1+ homogenization for liver magnetic resonance imaging (MRI) at 7T. The current findings at 7T may have implications for body imaging applications in clinical settings at 3T where B1+ inhomogeneities are also known for degrading image quality in the torso.